2022
DOI: 10.3390/ijerph192416708
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Footprint of Away-From-Home Food Consumption in Brazilian Diet

Abstract: Environmentally unsustainable diets are often characterized by being high in calories, processed foods, and red meats, characteristics related to away-from-home food (AFHF). The aim of this study is to evaluate if AFHF consumption is related to environmental sustainability. Data of 20,780 adults from 24 h recalls collected in the 2017–2018 Brazilian National Dietary Survey (NDS) were used to estimate carbon footprint coefficients. The mean carbon footprint was estimated among individuals who consumed AFHF and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Differences also occur as there is a lack of detailed data on out-of-home food expenses in the household survey, although we perform analyses adjusted for the percentage of out-of-home spending due to this absence and present results per 1•000 kcal. A study conducted in urban areas of Brazil found that out-of-home food consumption was positively associated with increased atmospheric GHG, regardless of age and income (42) . Besides these findings, more studies incorporating different indicators are necessary for a global picture of the impact of ultra-processed foods on the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Differences also occur as there is a lack of detailed data on out-of-home food expenses in the household survey, although we perform analyses adjusted for the percentage of out-of-home spending due to this absence and present results per 1•000 kcal. A study conducted in urban areas of Brazil found that out-of-home food consumption was positively associated with increased atmospheric GHG, regardless of age and income (42) . Besides these findings, more studies incorporating different indicators are necessary for a global picture of the impact of ultra-processed foods on the environment.…”
Section: Discussionmentioning
confidence: 99%